2019
DOI: 10.1590/s0004-2803.201900000-41
|View full text |Cite
|
Sign up to set email alerts
|

Historical Perspective of Gastroesophageal Reflux Disease Clinical Treatment

Abstract: BACKGROUND: Gastroesophageal reflux disease (GERD) is one of the most prevalent gastrointestinal diseases. GERD generates significant impairment in patients’ quality of life and it is associated to relevant medical resources utilization. A better understanding of GERD pathophysiology in the past five decades has favored the evolution of therapeutic strategies from non-drug interventions and antacids to more efficacious and safer alternatives. OBJECTIVE: To summarize data about the historical evolution of GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
10
0
5
Order By: Relevance
“…Recent epidemiological studies showed there was increasing GERD prevalence worldwide [3]. The worldwide [1,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent epidemiological studies showed there was increasing GERD prevalence worldwide [3]. The worldwide [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…The heartburn can radiate to the neck and it is aggressive after meals or during lying down position [ 2 ]. GERD has also extra-esophageal symptoms like chronic cough, asthma, and sometimes tissue lesions [ 3 ]. GERD has unknown causes, it is mostly caused by multifactorial pathogenesis like esophagogastric junction dysfunction, hypersensitivity of the esophagus, impaired esophageal bolus transit, and high intragastric pressure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, o aumento Brazilian Journal of Health Review, Curitiba, v.4, n.3, p. 14245-14253 may./jun. 2021 da prevalência também pode ser explicado devido aos avanços dos métodos diagnósticos e do melhor entendimento das características da doença (ZATERKA et al, 2019).…”
Section: Epidemiologiaunclassified
“…Evolution of GERD treatment in Brazil. Modified from Zaterka et al (2019)[11] H2RAs -histamine H2-receptor antagonists, P-CABs -potassium-competitive acid blockers, PPI -proton pump inhibitors.…”
mentioning
confidence: 99%